The phytotoxicity of soils in urban landscapes of Mariupol city - Miroshnychenko, M.M.; Krivitska, I.A. (AgroChemistry and Soil Science, 2016)
The research is based on a comparison of chemical analysis of soils at monitoring sites in Mariupol in 2008 and 2013. Due to the high lateral and radial heterogeneity of soil cover in the city, the using of traditional monitoring methods is not enough objectively reflecting change of the ecological status of soils. The accumulation of some chemical elements, such as manganese, nickel, lead, zinc and compounds of phosphorus, potassium, chlorine detected in the soil near industrial enterprises and in residential areas. The phytotoxicity of soils under various levels of contamination has been investigated using test crops of corn and radish. Both test culture and their diagnostic organs show similar results. In turn, the calculated aggregate contamination index Z is not enough closely correlate with phytotoxicity, because not all of pollutants are taken into account. Three levels of soil contamination by heavy metals and mineral salts were identified by using cluster analysis: where toxic effect does not appear at all (1), it increases up to 20-30 % (2) or reaches 40-50 % (3). The impact of contamination on the growth of higher plants is most evident near metallurgical combine "Azovstal". Cleanest areas are related to grassy lawns in the central part of the city where the soil material from the outside was used. Thus, determination of phytotoxicity significantly complements results of chemical-analytical control and improves reliability of soil monitoring in urban landscapes.